An overview of anxiety levels of Muhammadiyah citizens against COVID-19 vaccination in Surabaya - Siti Aisyah; Ira Purnamasari; Uswatun Hasanah; Dede Nasrullah; Vika Ramadhana Fitriyani (Universitas Muhammadiyah Surabaya, 2023)
Since the publication of PERMENKES Number 10 of 2021 on the implementation of vaccinations in the context of the COVID-19 pandemic, the community, particularly Muhammadiyah residents, has responded. Most Muhammadiyah residents do not have anxiety about COVID-19 vaccination because people are starting to realize the importance and benefits of vaccination. Even though vaccination activities have been going on for a long time, there are still people who feel anxious about the COVID-19 vaccination. The anxiety experienced by respondents is a natural thing because the current pandemic is a new type of disease that has never been experienced before. Numerous media outlets produce a lot of news that has the potential to change how the public feels about vaccines. Anxiety can be brought on by the general public's poor impression of immunizations. The process of immunizing will be hampered by the onset of fear. The study aimed to describe the amount of COVID-19 vaccination-related anxiety among Muhammadiyah inhabitants in Surabaya. This study, a descriptive study with 100 respondents, used probability sampling using a stratified random sampling technique. The DASS-42 questionnaire was utilized as the data-gathering tool. The findings revealed that 77 persons (77 percent) and 23 people did not experience any abnormal levels of vaccination fear (23 percent).Â According to the study's findings, the majority of Muhammadiyah inhabitants did not experience fear related to receiving a COVID-19 immunization since people were starting to understand the significance and advantages of vaccination. Although COVID-19 immunization campaigns have been ongoing for a while, some people still experience anxiety. Respondents' fear is understandable given that the present epidemic is a brand-new disease that has never been seen before.